Catalytic transfer hydrogenation of ethyl levulinate into γ-valerolactone over air-stable skeletal cobalt catalyst. Issue 2 (April 2022) - Ren, Dezhang; Zhao, Ce; Zhang, Nahui; Norinaga, Koyo; Zeng, Xu; Huo, Zhibao
Abstract: A fast and easy handled batch air diffusion method (BA) was developed to obtain a non-pyrophoric, air-stable skeletal Co catalyst (A-SCo) for catalytic transfer hydrogenation (CTH) of ethyl levulinate (EL) into γ-valerolactone (GVL). A batch air diffusion method (BA) consumed the active adsorbed H2 on the surface of skeletal Co (SCo) but maintained structure catalyst and avoided excessive oxidation of metallic Co, Ni and Al. The 96% yield of GVL was obtained over the A-SCo and HZSM-5 at 140 °C. Further study of CTH process shows that metallic state of A-SCo provides important active sites for dehydrogenation of i -PrOH, which is critical step for hydrogenation of EL. This study provides a simple, efficient method to prepare an air-stable skeletal metal catalyst for CTH and hydrogenation process. Graphical Abstract: ga1 Highlights: Air-stable skeletal Co catalyst was prepared by a simple air-pretreated method. The batch air diffusion process maintains the structure and metallic state of skeletal Co. The 96% yield of γ-valerolactone was obtained over air-stable skeletal Co and HZSM-5. Prepared skeletal Co could be reused several times without the loss of its activity.